An approach to the digital divide in Costa Rica from the point of view of access, connectivity and digital literacy - Muñoz Alvarado, María Daniela (2014)
The purpose of this paper is to analyze the current state of the digital divide in Costa Rica through a bibliographic review on the issues of access to technology, connectivity and digital literacy. Thus, the article presents an introduction to the concept of digital divide, its status in Costa Rica and comprehensive data on access to information technology and communication, connectivity and digital literacy. It also makes a synthesis of the various projects and institutions that collaborate in reducing the digital divide in the country. It is concluded that efforts are not enough and are disconnected. The involvement of various institutions is necessary to reduce the digital divide as well as using ICT as a real tool for the empowerment of the individual and of the information society.